Costing for the Fashion Industry - Evans, Nathalie; Jeffrey, Michael (New York : Bloomsbury, 2020)
"Costing for the Fashion Industry is a practical, easy-to-use guide to the manufacture, sourcing and risk management methods essential to make a new fashion business venture financially viable. Each chapter focuses on a theme, such as entrepreneurship, time constraints, global awareness and new markets and sourcing, alongside practical exercises and detailed industry case studies to put the theory into context. This second edition explores capital investment decisions, the changing nature of cost and the importance of global awareness and new markets, as well as expanded coverage of internationalization strategies for SMEs"--
Previous edition entered under: Michael Jeffrey.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Clothing trade -- Costs; Fashion merchandising